2013
DOI: 10.1542/peds.2012-2595
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Trends in Peer Victimization and Emotional Distress in LGB and Heterosexual Youth

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Peer victimization predicts numerous health risks. Lesbian, gay, and bisexual (LGB)-identified youth report greater peer victimization than do heterosexualidentified youth. No longitudinal studies have been conducted on developmental trends of peer victimization and emotional distress among LGB and heterosexual youth. WHAT THIS STUDY ADDS:We provide the first longitudinal evidence on developmental trends of peer victimization and emotional distress for LGB-and heterosexual-identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
2
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 33 publications
7
82
2
11
Order By: Relevance
“…However, our results contrast with recent work which has suggested that LGB individuals are now living 'beyond the closest' (Seidman, 2002), where concealing a LGB identity is no longer a major preoccupation for LGB youth (Seidman, 2002;Willis, 2012). Furthermore, although LGB victimization is still acknowledged as a major issue for many LGB young people (Chesir-Teran 2011), recent research has suggested this victimization decreases over time (Robinson, Espelage, & Rivers, 2013).…”
Section: Limitationscontrasting
confidence: 99%
“…However, our results contrast with recent work which has suggested that LGB individuals are now living 'beyond the closest' (Seidman, 2002), where concealing a LGB identity is no longer a major preoccupation for LGB youth (Seidman, 2002;Willis, 2012). Furthermore, although LGB victimization is still acknowledged as a major issue for many LGB young people (Chesir-Teran 2011), recent research has suggested this victimization decreases over time (Robinson, Espelage, & Rivers, 2013).…”
Section: Limitationscontrasting
confidence: 99%
“…Hillier & Harrison, 2004;Safren & Rogers, 2001) LGB participants in our study experienced abuse and discrimination when their homosexuality was either suspected or disclosed. However, our results contrast with recent work which has suggested that LGB individuals are now living 'beyond the closest' (Seidman, 2002), where concealing a LGB identity is no longer a major preoccupation for LGB youth (Seidman, 2002;Willis, 2012 Felix, Furlong, & Austin, 2009;Russell, Ryan, Toomey, Diaz, & Sanchez, 2011), recent research has suggested this victimization decreases over time (Robinson, Espelage, & Rivers, 2013).…”
Section: Limitationscontrasting
confidence: 99%
“…Very few UK or European studies have directly quantified the underlying minority stress and other mechanisms for sexual orientation-related mental health disparities though available findings support those from US studies. A recent UK longitudinal study found that early victimisation partially explained emotional distress disparities in LGB young people (Robinson et al, 2013) and other minority stress mechanisms involving negative experiences of 'coming out' and homophobic bullying have been associated with increased odds of suicidal thoughts and attempts (Nodin et al, 2015). UK attitudes towards homosexuality have become increasingly tolerant; however, experiences of homophobia and victimisation remain common (Guasp, 2012;Guasp, 2013).…”
Section: Introductionmentioning
confidence: 99%